Experiências formativas de estudantes de licenciatura da Universidade Estadual de Feira de Santana no campo do desenvolvimento humano, mediante oficinas de Biodança - Ferreira, Rands Tadeu Palma (2025)
This dissertation communicates the results of research that aimed to: understand the formative experiences of undergraduate students in the field of human development, with the practice of Biodanza (Toro, 2002; 2009; 2014). From a theoretical-methodological point of view, it is based on the assumptions of Edgar Morin's (2006) complex thinking and the qualitative design according to Minayo and Costa (2018). Three data production devices were applied (field diary, explanatory interview and questionnaire) to a group of 10 of the total 15 participants. The analysis was based on the application of techniques and procedures that are close to what the Grounded Theory method recommends (Strauss; Corbin, 2008). Eight categories emerged from this process: Manifesting Initial Difficulties during the Practice of Biodanza, Strengthening Personal Identity, Expanding Consciousness, Awakening a Potential of Life, Experiencing Corporeity, Developing Life Potentials, Strengthening Bonds and Pointing out Biodanza Perspectives. From the aggregation of these categories emerges the phenomenon Contributing to Human Development. The process of understanding the formative experiences of the research participants culminated in the configuration of the substantive theory, which is characterized by bringing together factors that communicate, touch each other deeply and integrate, forming a model whose movements of each of them are sometimes particularized and sometimes universalized, demonstrating the complexity of their nature. By bringing together in its structure the meanings that the subjectivities of each participant reveal, this model proves to be a resource that helps to illuminate the path that each person must follow in search of their evolution. As this is research developed in Line 2 of the Postgraduate Program in Education (PPGE), we believe that this practice can be a strategic alternative to be introduced into the curriculum, in the training process of undergraduate students at the State University of Feira de Santana (UEFS), contributing to self-knowledge through body expression (movement/dance), in order to develop their genetic potential and guide their future pedagogical practices.